2014
DOI: 10.1007/s11136-014-0625-8
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of the Iranian version of the QAPACE in adolescents

Abstract: Our results support the initial reliability and validity of the Iranian version of QAPACE as a daily physical activity measure in adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…For each activity f(i), d(i) and m(i) correspond to its daily frequency, mean duration and intensity respectively according to the physical activity compendium, SP and VP correspond to school period and vacation period respectively [ 22 ]. Before using this questionnaire for the current study, the QAPACE questionnaire was translated into Persian, and the reliability and validity of the Iranian version was tested, with results showing acceptable reliability and validity [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…For each activity f(i), d(i) and m(i) correspond to its daily frequency, mean duration and intensity respectively according to the physical activity compendium, SP and VP correspond to school period and vacation period respectively [ 22 ]. Before using this questionnaire for the current study, the QAPACE questionnaire was translated into Persian, and the reliability and validity of the Iranian version was tested, with results showing acceptable reliability and validity [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…The questionnaire was easy to use and convenient, measuring activities at school, on vacation and at home. Reliability and validity of this questionnaire have been assessed in Iranian children and adolescents ( 17 ) .…”
Section: Methodsmentioning
confidence: 99%
“…Developing a new tool or translation of available ones are options for researchers to investigate the concept of participation in occupations. Reviewing the Persian tools for assessing adolescent’s participation in occupations have shown that only seven tools (Modifiable Activity Questionnaire (Delshad et al, 2015), Child Assessment of Participation and Environment (CAPE) (Amirian et al, 2015), Assessment of Life Habits (Life_H) (Mortazavi, et al, 2014), Quantification de l’Activite Physique en Altitude Chez Les Enfants (Amiri et al, 2014), self-efficacy questionnaire regarding leisure time physical activity (SELPA) (Abasi et al, 2016a), self-regulation scale about leisure time physical activity (SRLPA) (Abasi et al, 2016b), and adolescent social participation questionnaire (Afshani and Janatifar, 2016)) are available. A review of these tools shows that none encompasses all areas of the daily occupations comprehensively.…”
Section: Introductionmentioning
confidence: 99%